Analisis Kinerja Keuangan Pemerintah Kota Balikpapan Ditinjau Dari Anggaran dan Realisasi Pendapatan Asli Daerah (Jurnal Ilmu Akuntansi Mulawarman (JIAM), 2018)
ABSTRACTJulianty Siahaan, 2017. Analysis of Financial performance of the Government in the city of Balikpapan in terms of budget and Revenue Realization of the original area. Under the guidance Mr. Rande Samben and Mrs. Dhina Mustika Sari.This study aimed to find out how the financial performance of the Government in the city of Balikpapan in terms of budget and Revenue Realization of the original area. This research was conducted in the city of Balikpapan, East Borneo province using data budget and Income Realization since 2013-2016, obtained from the agency concerned. The result of calculation by using the formula of income budget variance analysis of financial performance Revenues the Government's Native City of Balikpapan for the years 2013-2016 has reached the specified target with an average of 96.82%. The financial performance of the regional government's original Revenue Balikpapan City seen from the analysis of the original revenue growth Area year 2013 up to 2016. Due to his percentage each year is decreasing. The financial performance of the regional government's original Revenue Balikpapan City seen from analysis of financial ratios pointed out that the degree of decentralization of Balikpapan City fall into the category of being, that is, with an average of 24.65%. Balikpapan City independence can be said to be low but have almost reached the category of moderate or considerable, it was shown with an average ratio of financial independence of the region namely of 49.19%. Governments city of Balikpapan is said to be quite effective in achieving acceptance of the PAD against the budgeted average of 89.66%. The efficient level of Balikpapan City can be said to be highly efficient with an average of 3.27%. The degree of local tax contribution towards acceptance of the PAD is already quite well with average 71.88% levy on contributions to the area, still less the average 9.47%, as well as LOCAL contributions are still less well with average 3.32%, further contributions to the acceptance of other legitimate PAD also still less contribute to the acceptance of the PAD that is with an average of 15.32%.Key words: financial performance, budget, realization, Original Income area.